Sinergi Pendidikan Perguruan Tinggi dan SMK dalam Pengembangan Ilmu Akuntansi - Nurrasyidin, Muhammad; Nugroho, Arif Widodo; Fikri Hidayat; Sumarso (Kilau Publishing, 2024)
This service is carried out with the intention of finding harmony between universities and vocational schools in the field of accounting. This is done so that vocational school graduates have a solid knowledge of accounting. The method employed in delivering the material is primarily the lecture method, which is designed to provide a comprehensive explanation of the subject matter. To enhance understanding and encourage active participation, the session concludes with a question-and-answer segment, allowing participants to seek clarification and engage in discussions about the topics presented. There was enthusiasm from the participants who attended this activity. In addition, the teachers and school leaders of SMK Muhammadiyah 4 Slipi Jakarta were very enthusiastic about the activities carried out by lecturers from the UHAMKA Faculty of Economics and Business. They hope that this synergy can continue to run well, so that there is continuity between levels of education and there is no gap in the same field of science. The alignment between higher education institutions and vocational high schools plays a crucial role in producing graduates who are proficient in their respective fields of expertise. Such synergy ensures that students possess a solid foundation of knowledge and skills, enabling them to transition seamlessly into higher education without requiring prolonged periods of adaptation. Moreover, graduates from vocational high schools are often better equipped for the workforce, demonstrating a competitive advantage over those from general education schools due to their specialized training and practical experience